2023
DOI: 10.1007/s12665-023-10762-0
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality assessment along the West of New Damietta Coastal City of Egypt using an integrated geophysical and hydrochemical approaches

Abstract: Recently, the groundwater became very important source for the Egyptian water balance. Therefore, assessing its quality and quantity is necessary before initiating any developmental plans using this resource. In this research, a new operated power plant, which is located in the coastal area of West New Damietta City, north-east of Egypt was designed to work using the coastal groundwater aquifer. Therefore, an integrated approaches of both geophysical methods and hydrochemical analysis were applied to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The primary supply of freshwater for a variety of applications is groundwater [3,4]. Prior research found that 26% of the world's sustainable freshwater sources come from groundwater [5].…”
Section: Introductionmentioning
confidence: 99%
“…The primary supply of freshwater for a variety of applications is groundwater [3,4]. Prior research found that 26% of the world's sustainable freshwater sources come from groundwater [5].…”
Section: Introductionmentioning
confidence: 99%
“…Geochemical processes arising from interactions between aquifers and water play a pivotal role in governing groundwater quality, especially in regions with limited recharge from rainfall, where it serves as a vital resource for domestic and agricultural needs [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%